114 Cancer-Related Proteins in Lung Tissue from Uranium Miners - Variation by Occupational Exposure and Subtype of Lung Cancer. (11th October 2013) - Casjens, S C; Stricker,; Westerwick,; Taeger,; Rabstein,; Wiethege,; Tannapfel,; Brüning,; Johnen,; Pesch,
Abstract : Objectives: We investigated the association of cumulative exposure to radon and arsenic with cancer-specific proteins in lung tissue from uranium miners. Methods: Paraffin-embedded lung tissue of 147 miners was randomly selected from a biobank established for German uranium miners comprising adenocarcinoma (AdCa), squamous cell carcinoma (SqCC), small cell lung cancer (SCLC), and cancer-free tissue. Within each stratum, we additionally stratified by level of cumulative exposure to radon and arsenic. Lifetime exposure to radon and arsenic was estimated using a job-exposure matrix developed for uranium mining in Germany. For 22 cancer-related proteins, immunohistochemical scores were calculated from the intensity and percentage of stained cells. The association of these scores with exposure to radon and arsenic was explored by Spearman rank correlation coefficients (rs ). We further applied supervised and unsupervised classification to investigate protein patterns by type of lung tissue. Results: Occupational exposure was associated with an up-regulation of NOTCH1 (radon: rs = 0.18, 95% CI 0.02–0.33; arsenic: rs = 0.23, 95% CI 0.07–0.38). MUC1 classified lung cancer from cancer-free tissue (failure rate of 2.1%), and HIF1A and NKX2–1 discriminated the major subtypes of lung cancer with a failure rate of 8.4%. Conclusions: These results suggest that the radiation-sensitive protein NOTCH1 can be up-regulated in lung tissue from uranium miners by level of exposure to pulmonary carcinogens. The distinct phenotypes of the major subtypes of lung cancer could be discriminated with cancer-related proteins.